Poisoning by Senecio brasiliensis in Horses in Northern Rio Grande do Sul - Leite Dau, Stéfano; Machado, Tanise Policarpo; dos Santos, Ezequiel Davi; Setim, Diorges Henrique; Sakis, Eduardo Rebelato; Alves, Leonardo Porto; da Motta, Adriana Costa (Acta Scientiae Veterinariae, 2019)
Background: In various regions of Brazil, horses and cattle are considered the most susceptible animals to plant poisoning. The plants of the genus Senecio are the most important in Rio Grande do Sul because they have the active principle known as the pyrrolizidine alkaloid. Its diagnosis is made through epidemiology, clinical signs and histopathological analysis, either of the tissues obtained by biopsy or necropsy. The objective of this study was to report and characterize the epidemiological, clinical and anatomopathological findings of three cases of natural poisoning by Senecio brasiliensis in horses assisted at the Hospital Veterinário (HV) of the Universidade de Passo Fundo (UPF). Cases: Three traction horses, two males and one female, were admitted at the HV-UPF for clinical care. The animals were presenting anorexia, weight loss, dysmetria, proprioceptive deficit and signs suggestive of colic. The epidemiological study revealed that the sites where these animals were located were infested by Senecio brasiliensis. The support therapy used for equine colic in all three cases was unsuccessful. One of the animals died and the other two were euthanized, all three of them being reffered for necropsy. The post-mortem findings were mainly found in the liver, which showed accentuation of the lobular pattern and the appearance of nutmeg. During necropsy, fragments of organs from thoracic and abdominal cavities and central nervous system were collected and fixed in 10% buffered formalin. Subsequently, the samples were processed chemically, submitted to cuts of five micrometers of thickness and stained with hematoxylin and eosin for microscopic analysis. Microscopically, the liver of all three horses presented megalocytosis, fibrosis and bile ducts hyperplasia. In the central nervous system, spongiosis and the presence of Alzheimer type II astrocytes were observed. Thus, through the association of information, the diagnosis of poisoning by Senecio brasiliensis was achieved. Discussion: The diagnosis of natural poisoning by Senecio brasiliensis was obtained through the epidemiological survey that showed S. brasiliensis in pastures where all three horses were allocated. Cases of intoxication by S. brasieliensis in cattle are more frequent than in equines, although both species are considered the most susceptible. In horses, the main clinical manifestations observed include neurological disorders, apathy, anorexia, dysphagia, weight loss, subcutaneous edema and icterus. The clinical signs presented by the equines suggested initial signs of colic syndrome, although anorexia, weight loss, dysmetria and proprioceptive deficit are commonly observed in pyrrolizidine alkaloid poisoning in the liver, both in cattle and horses. The pyrrolizidine alkaloids present in the genus Senecio that become toxic when biotransformed in the liver into a pyrrholic form highly reactive that inhibits cell mitosis and leads to the onset of megalocytosis, cell death and liver fibrosis. The necropsy findings and histopathology were characteristic of poisoning in equines, since the predominant macroscopic lesions in the liver were hepatomegaly and accentuation of lobular pattern, whereas microscopically, there was a predominance of hepatic fibrosis, megalocytosis, spongiosis and the incidence of Alzheimer's type II astrocytes in the brain. These lesions are observed both in natural and in experimental cases of poisoning in horses. Thus, through the ante-mortem and complete post-mortem evaluation of the three equines, it was possible to establish the occurrence of natural poisoning by Senecio brasiliensis in Northern Rio Grande do Sul, as well as to characterize the epidemiological, clinical and anatomopathological findings of poisoning in this species.